Mathematics Learning for Students of Basic Age: Montessori Theory Applicative Review - Muhammad Shaleh Assingkily (Yayasan Zia Salsabila, 2024)
Although previous studies have discussed about the theme of Montessori theory in learning mathematics, but the focus of studying in basic age students needs to be done in depth. Because, basic age children are seen as crucial age in teaching concrete and critical thinking skills using the Montessori method. This study aims to describe how the Montessori method in learning mathematics. The research procedure is carried out based on literature or literature studies. The results of the study found that operationally the application of the Montessori method in mathematics learning: First, the introduction of identity that can be done by making a relationship between the visual aspects of an object and its name. Second, recognition of comparison. This step is carried out to find an affirmation of the level of student understanding of the material. Third, make a variety of visualizations but allied and require students to be able to explain it. With the steps that provide attention to the development of the learning reasoning will gradually reduce the